One-Year Review of the SCREEN (Skin Cancer Post-Transplant) Clinic: What We Have Learned. Issue 1 (January 2017) - Baldwin, Sarah; Au, Sheila
The Skin Cancer Post-Transplant (SCREEN) Clinic is a skin-cancer screening clinic that is fully integrated into the renal transplantation clinic at St Paul's Hospital in Vancouver, British Columbia. The purpose of this review was to determine characteristics of patients most at risk for skin cancer, to specify types and locations of skin cancers diagnosed, and to identify areas for patient and physician education. Transplant patients (91% renal; 5% heart) screened by a dermatologist during a 12-month period were stratified into low-, medium-, and high-risk groups based on detailed history and skin examination. In total, 118 skin cancers were diagnosed. White males were found to be most at risk. Squamous cell carcinoma accounted for the majority of tumours, over 25% of which demonstrated invasion. Forty-two percent of patients used only 1 to 2 bottles of sunscreen per year, and sun-protective practices were limited. With this information, we have identified potential target areas for patient and physician education.